Intestinal obstruction after surgery for congenital biliary dilatation in children: diagnosis and management - Liu, Zhen-sheng; Bian, Jian; Yang, Yong; Wei, De-cheng; Qi, Shi-qin (Frontiers in Pediatrics, 2025)
ObjectiveTo analyze etiologies and management of postoperative intestinal obstruction following surgery (exeision of the dilated bile duet and Roux-enY hepaticojejunostomy) for congenital biliary dilatation (CBD) in children.MethodsA single-institution retrospective review was conducted on 475 patients who underwent Roux-en-Y hepaticojejunostomy following complete excision of the dilated bile duct. Among the cohort, nine patients underwent reoperation for intestinal obstruction. The perioperative data of these cases were thoroughly analyzed.ResultsThe cohort (8F:1M) developed obstruction 20 days-8.8 years postoperatively. Primary etiologies included internal hernias (Petersen's:2, transverse mesocolic:3, Brolin's:1), biliary-jejunal loop torsion (1), and adhesions (2). Three patients underwent redo biliary-enteric anastomosis secondary to Roux-en-Y loop necrosis. Cross-sectional imaging in children with internal hernia or Roux-en-Y volvulus demonstrated distended, fluid-filled biliary-jejunal loops at the porta hepatis. Surgical indications for intestinal obstruction included peritoneal signs, aggravated abdominal pain, and failure of conservative treatment. Two children with intestinal obstruction had abnormal liver function tests preoperatively.ConclusionInternal hernias (particularly within the internal hernia triangle) are the predominant cause of post-CBD surgery obstruction. Cross-sectional imaging shows high diagnostic sensitivity. Given the higher likelihood of internal hernia as a cause of post-CBD surgery obstruction and its rapid progression to Roux limb necrosis, early surgical intervention should be considered.